Capital Management on Profitability: Study of Family Companies in the Food and Beverages Sector Listed on the Stock Exchange Indonesian Effects 2018-2022 - Made Wedaswari; Sari Widati; Maulina Rizky (International Journal Business, Management and Innovation Review, 2024)
Working  capital  management  is  very  important  for  businesses  because  working  capital  management  includes  managing  business  operational  activities.  Effective  working  capital  management  can  increase  business  profitability.  Meanwhile,  poor  working  capital  management  can  lead  to  lower  profitability,  even  losses.  Companies  suffering  from  these  losses  grow  every  year.  Although  it  is  known  that  the  number  of  companies  listed  on  the  Indonesian  Stock  Exchange  in  this  sector  is  increasing  every  year.  Therefore,  this  research  was  conducted  to  detect  and  find  evidence  of  the  impact  of  working  capital  management  which  includes  average  maturity,  inventory  conversion  period,  debt  moratorium  and  cash  flow  activities  on  the  profitability  of  family  businesses  in  the  food  and  beverage  sector.  listed  on  the  stock  exchange.  Indonesia  Stock  Exchange  for  the  period  2018  -  2022.  The  sampling  method  used  was  an  intentional  sampling  method  obtained  from  25  companies  with  a  sample  size  of  125.  The  data  analysis  technique  used  multiple  regression  analysis.  The  research  results  show  that  the  average  delivery  time  and  inventory  conversion  time  have  a  significant  and  negative  effect  on  profitability.  At  that  time,  the  debt  moratorium  had  a  positive  but  insignificant  impact  on  profitability. Meanwhile,  operating  cash  flow  has  a  positive  and  significant  effect  on  profitability.